2014
DOI: 10.1080/00036846.2014.887197
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the heterogeneous income elasticity and dynamics of health expenditure

Abstract: In this article, we empirically study the impact of per capita income on health-care expenditure and its dynamics over time in a sample of 14 OECD countries for the period 1971 to 2009. A simple model, built upon one developed by Newhouse (1977), suggests that health care is a necessity in the short run but it cannot be rejected to be a luxury good in the long run. Our findings provide strong empirical evidence that a year's health expenditure is conditioned by the previous one. Interestingly, our results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 40 publications
4
26
1
Order By: Relevance
“…Existing studies have used two main methods to explore this heterogeneity. One involves grouping sample countries according to either their level of economic development or the sample period and then employing an empirical analysis for each group (see, e.g., Okunade & Suraratdecha, ; Di Matteo, ; Chakroun, ; Farag et al, ; Blazquez‐Fernandez et al, ). The other involves using nonparametric, semiparametric, or quantile regression methods to detect the varying effects of factors (see, e.g., Di Matteo, ; Chen, Lin, & Chang, ; Liu, Li, & Wang, ; Yu, Wang, & Chang, ; Chen, Vargas‐Bustamante, Mortensen, & Thomas, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have used two main methods to explore this heterogeneity. One involves grouping sample countries according to either their level of economic development or the sample period and then employing an empirical analysis for each group (see, e.g., Okunade & Suraratdecha, ; Di Matteo, ; Chakroun, ; Farag et al, ; Blazquez‐Fernandez et al, ). The other involves using nonparametric, semiparametric, or quantile regression methods to detect the varying effects of factors (see, e.g., Di Matteo, ; Chen, Lin, & Chang, ; Liu, Li, & Wang, ; Yu, Wang, & Chang, ; Chen, Vargas‐Bustamante, Mortensen, & Thomas, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To meet our aims, we use a balanced panel of data from 28 OECD countries over the period of 1990–2012 and apply a quantile regression method for panel data with fixed effects. Moreover, recent studies have found that HCE in a given year is conditioned on the previous year, indicating the existence of an “anchorage effect” (“expenditure inertia”; see, e.g., Okunade & Suraratdecha, ; Lago‐Peñas, Cantarero‐Prieto, & Blázquez‐Fernández, ; Blazquez‐Fernandez, Cantarero, & Perez, ; Castro, ). We capture this kind of effect by including the lagged dependent variable in our models.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is likely that the elasticity of pharmaceutical expenditure differs across countries as is observed in past literature on health expenditures. Prior literature that investigates elasticity of health expenditure usually assesses heterogeneity by simply segmenting countries into income groups, development levels, health spending, and time periods (Blazquez‐Fernandez, Cantarero, & Perez, ; Farag et al, ). We extend the investigation of effect heterogeneity in several ways by considering (a) different quantiles of the response variables and (b) politico‐economic freedom of countries.…”
Section: Effect Heterogeneitymentioning
confidence: 99%
“…Some categories such as patient choice of providers (3), cost reducing innovations (6), and the reduction of fraud (8) and waste (9) have been hardly mentioned or studied. We conclude the same for important underlying cost drivers such as wages (21) and capital (11). Demand policies make up 17% of all cost containment policy proposals (387 of 2250).…”
Section: Resultsmentioning
confidence: 79%
“…The US, for example, has the highest level of health expenditures of all countries, but on average performs rather poorly on health outcomes [9,10]. Some studies suggest that the level of health spending does not fully account for differences in health outcomes among OECD countries, suggesting substantial room to improve value for money [11,12].…”
Section: Introductionmentioning
confidence: 99%